Comparing Religious Moderation Strategies: P5 vs. P5-PPRA in Elementary Schools - Noptario; Sulfiani, Sulfiani; Mohammad Yusuf Randy; Alia Latifah; Syamela Massa Kaulika; Zakaria, ABD Razak (Badan Litbang dan Diklat Kementerian Agama RI, 2024)
Indonesia, as a multicultural nation with diverse cultures, ethnicities, races, and religions, emphasizes the importance of tolerance and mutual respect among its people to prevent conflicts. One approach to achieving this is by enhancing religious moderation values. In the context of elementary schools and madrasah ibtidaiyah, the Pancasila Education (P5) and Pancasila and Religious Education (P5-PPRA) programs play a central role. The aim of this study is to compare the effectiveness of the P5 and P5-PPRA programs in improving religious moderation. This study employs a quantitative approach with data collection through questionnaires. Respondents consisted of 100 students and 8 teachers at Kanisius and Madrasah Ibtidaiyah during the 2023/2024 academic year. The data were validated and analyzed using the Paired Sample T-test. The analysis results showed a significant value (2-tailed) of 0.000 < 0.05, indicating a significant relationship between P5 (at Elementary Schools) and PPRA (in Madrasah Ibtidaiyah) in enhancing religious moderation. The average score of P5 is 74.30, while P5-PPRA is 87.20, with an average difference of 12.91. This indicates that the P5-PPRA program is more effective in strengthening religious moderation in schools. This finding suggests that students at Madrasah Ibtidaiyah exhibit higher tolerance and appreciation for diversity compared to students at Kanisius schools. These findings can be utilized by policymakers and educators to improve religious moderation programs by adopting and integrating P5-PPRA elements, thereby creating a more inclusive and tolerant learning environment.